Pengembangan Media Pembelajaran Terintegrasi Ayat-Ayat Alquran Berbasis Makromedia Flash untuk Mata Pelajaran Fisika - Zainuddin, Zainuddin; Kadir, Abdul; Halmuniati, Halmuniati; Asmin, La Ode; Isa, La; Rafiqah, Rafiqah (Institut Agama Islam Negeri Kendari, 2023)
This study aims to determine the feasibility of learning media based on macromedia flash integrated Al-Qur'an verses that were developed in MAN 1 Konawe students. This research is a type of research and development (research and development) with a development design according to Borg & Gall. The trial participants were 21 students of class X MAN 1 Konawe, the data collection instrument used a questionnaire, interviews, test questions, and observation sheets. Data analysis and product development trials consist of qualitative analysis and quantitative analysis. The results of this study indicate that: Integrated Flash Macromedia-Based Physics Learning Media with Qur'anic Verses at the developed MAN 1 Konawe school can be declared to meet the aspects of validity, reliability that is good and feasible to use.